Analysis of rural OTN network planning and networking architecture - Wenyue CHEN; Yuneng CHEN; Cheng CHEN; Tingjing ZHANG (Dianxin kexue, 2020)
Optical transport network has become one of the mainstream technologies for transport networks with its technological advantages.The previous OTN was mainly deployed in the county and above.With the vigorous development of family broadband services in rural,it is necessary to sink OTN to the level of rural to meet the needs of rapid development in rural areas.Based on the development of family broadband services,a variety of rural OTN system capacity measurement methods were provided and the best rural OTN system networking architecture was analyzed,which could play the reference and thought for the rural OTN in the related future research.